Unceasing kindness : a biblical theology of Ruth - Lau, Peter H. W.; Goswell, Greg (Downers Grove, Illinois : InterVarsity Press, 2016)
The Old Testament book of Ruth is understandably a firm favorite in the church for small-group study and preaching: a heart-warming story of loyalty and love, a satisfying tale of a journey from famine to fullness. In the academy, the book has been a testing ground for a variety of hermeneutical approaches, and many different ways of interpreting it have been put forward. However, the single interpretative lens missing is the one that is most beneficial for the church: biblical theology. While commentaries have adopted a biblical-theological approach of one form or another, there has not been a detailed treatment of the themes in Ruth from that perspective. Lau and Goswell's valuable New Studies in Biblical Theology volume aims to fill this gap. First, they focus on the meaning of the text as intended by the author for the original readers, but are mindful that the book is set within the wider context of Scripture. This context means not only the books surrounding Ruth in the canon, or even a particular section of Scripture, but also the rest of the Old Testament and the New Testament. Second, they discuss selected themes in Ruth, including redemption, kingship, mission, kindness, wisdom, famine, and the hiddenness of God. Within the overarching narrative of the Bible, from Genesis to Revelation, these themes can be viewed as different threads within the same cloth, or can be heard as different instrumental 'voices' within a symphony. Addressing key issues in biblical theology, the works comprising New Studies in Biblical Theology are creative attempts to help Christians better understand their Bibles. The NSBT series is edited by D. A. Carson, aiming to simultaneously instruct and to edify, to interact with current scholarship and to point the way ahead. - Publisher.
Introduction -- Reading Ruth in the early restoration period -- Ruth and the house of David -- Ruth as a wise woman -- Ruth and the Psalter -- Famine in Ruth -- God's hiddenness and human agency -- Redemption in Ruth -- Ruth and God's mission -- Conclusion.
Includes bibliographical references and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Theology